The Ewenki dialects of Buryatia and their relationship to Khamnigan Mongol - Khabtagaeva Bayarma (Harrassowitz, 2017)
Present research focuses on Mongolic loanwords in Ewenki dialects spoken in the territory of Buryatia. The aim of this work is to clarify the status of early Mongolic (i.e. not Buryat) and later Mongolic or Buryat layers. The introductory part of the book gives a short overview of the Ewenki dialects of Buryatia (Barguzin, Nercha, Baunt and North-Baikal), their language status, common phonetic and semantic features and differences between them. Also, a short survey is given on the Khamnigan Mongol language and its dialects, since the author considers this language the main source of Mongolic elements in Ewenki dialects.